2010
DOI: 10.1093/hmg/ddq478
|View full text |Cite
|
Sign up to set email alerts
|

Lack of WDR36 leads to preimplantation embryonic lethality in mice and delays the formation of small subunit ribosomal RNA in human cells in vitro

Abstract: Mutations in WD repeat domain 36 gene (WDR36) play a causative role in some forms of primary open-angle glaucoma, a leading cause of blindness worldwide. WDR36 is characterized by the presence of multiple WD40 repeats and shows homology to Utp21, an essential protein component of the yeast small subunit (SSU) processome required for maturation of 18S rRNA. To clarify the functional role of WDR36 in the mammalian organism, we generated and investigated mutant mice with a targeted deletion of Wdr36. In parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 74 publications
1
34
0
Order By: Relevance
“…WDR36 loss of function results in reduced levels of 18S rRNA in zebrafish (Skarie and Link, 2008). Knockdown of WDR36 expression causes a delay in processing 18S rRNA in mammalian cells, and loss of WDR36 in mice leads to preimplantation embryonic lethality (Gallenberger et al, 2011). Chi et al reported that mutant WDR36 directly affects axon growth of retinal ganglion cells in transgenic mice (Chi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…WDR36 loss of function results in reduced levels of 18S rRNA in zebrafish (Skarie and Link, 2008). Knockdown of WDR36 expression causes a delay in processing 18S rRNA in mammalian cells, and loss of WDR36 in mice leads to preimplantation embryonic lethality (Gallenberger et al, 2011). Chi et al reported that mutant WDR36 directly affects axon growth of retinal ganglion cells in transgenic mice (Chi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…All six UTPB proteins are universally conserved in eukaryotes and some have been associated with human diseases. For example, mutations of the human UTP21 gene are the causative agents of some forms of primary open angle glaucoma (20) and heterozygous deletion of the UTP6 gene is a candidate modifier of neurofibromatosis type 1 (21). …”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent studies have failed to replicate these findings. More recent studies suggest that genetic variants of WDR36 may alter POAG risk (Blanco-Marchite et al, 2011; Fan et al, 2009; Fingert et al, 2007; Frezzotti et al, 2011; Gallenberger et al, 2011; Hauser et al, 2006a; Hewitt et al, 2006; Janssen et al, 2013; Kramer et al, 2006; Miyazawa et al, 2007; Mookherjee et al, 2011; Pasutto et al, 2008; Ramdas et al, 2011a; Weisschuh et al, 2007). Knockdown of Wdr36 in zebrafish reportedly reduces levels of 18S rRNA, activates the p53 stress-response pathway, and is associated with ocular abnormalities (Skarie and Link, 2008).…”
Section: Genetic Linkage Analyses Of Poagmentioning
confidence: 99%